Caminhos Indiretos de Aprendizagem no Ensino de Biologia Celular para Alunos com Deficiência Visual Múltipla - Hell, Iara Belink (2020)
This research aims to discuss theoretical and practical aspects related to the learning of people with visual and multiple disabilities, with an emphasis on building paths, which by alternative means, can contribute to the development of these with regard